Silêncios em liberdade assistida : entre governamentalidades e estratégias de vida - Caser, Livia Pignaton (2014)
This research aimed to trace and question the crossings perceived during meetings with Creas’ (Social Assistance Specialized Reference Center) and with probation. Through dialogues, interviews and group talking, the intention was to locate, intensify crossings, lines on this field’s different facets and moments. The challenge was to “trace maps” with the intention of condense resonances with different times and territories. With some authors help, as Foucault and Costa, was founded the presence of a tangle of questions that interweaves with many other areas and spheres of activity that involves professionals, programs and State’s services purposes. On technician’s lines about daily actions, about encounters with families and adolescents in probation, on which crystalized points of view’s displacements were possible, in order to question practices and discourses, building a critical sight over this field. In addition, a brief historical study about how some concepts as family and “delinquency” population governmental intervention strategies. In addition, all of this enabled realize other ways of living probation, under practices and discourses of vigilance.